Unravelling Self-Efficacy in Online Discussion and Presentation: Insights from English Education Students in Kupang, Indonesia - Hornay, Priscilla Maria Assis; Ke Lomi, Aplonia Nelci (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
The rapid growth of digital technology has revolutionized the educational landscape, with online learning becoming a prominent mode of instruction. This study explores students' self-efficacy in the context of online discussions and presentations in English language learning. The research involved English Education students in Kupang, East Nusa Tenggara, Indonesia. Quantitative and qualitative data were collected through questionnaires and focus group discussions (FGDs). The questionnaire assessed students' self-efficacy beliefs in their speaking abilities and handling challenging situations during online discussions and presentations. The FGD provided more profound insights into the factors influencing students' experiences with virtual classroom speaking. The findings revealed that many students demonstrated a positive self-efficacy in their speaking abilities during online discussions. They expressed confidence in their communication skills and ability to handle complex tasks. However, limited access to internet connectivity, lack of engagement and social loafing, lack of preparation, students’ English Proficiency, and fear of making mistakes were demotivating factors affecting self-efficacy. The study highlights the importance of fostering a supportive online learning environment to enhance students' self-efficacy. To gain a better understanding of students' self-efficacy in online discussion and presentation, future research could include a more diverse group of students from various institutions and academic levels.